2019
DOI: 10.1108/ijebr-10-2018-0713
|View full text |Cite
|
Sign up to set email alerts
|

Does institutional logic matter in microfinance delivery? An empirical study of microfinance clients

Abstract: Purpose From an institutional theory perspective, the purpose of this paper is to investigate the combined impact of financial capital (microcredit) and human capital development (entrepreneurship training) delivered by financial non-governmental organisations (FNGOs) on the performance of micro and small enterprises (MSEs) in Ghana. Design/methodology/approach Adopting a multiple linear regression analysis, the study used primary data collected from 506 Ghanaian MSEs. Microcredit was measured using four mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 88 publications
(128 reference statements)
2
12
0
1
Order By: Relevance
“…The relationship between poverty alleviation and entrepreneurship training was statistically significant at the 0.001 level, and it was shown to be positive and strong in both districts. The result was matched with previous researchers (Atiase et al, 2019;Herath, 2015;Khanam et al, 2018;Mensah &Benedict, 2010 andNavirathan, 2018) also revealed that entrepreneurship training has a significant and positive impact on poverty alleviation. Micro-credit and poverty alleviation in both districts have a strong positive relationship and it was statistically significant at the 0.001 level.…”
Section: Correlation Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…The relationship between poverty alleviation and entrepreneurship training was statistically significant at the 0.001 level, and it was shown to be positive and strong in both districts. The result was matched with previous researchers (Atiase et al, 2019;Herath, 2015;Khanam et al, 2018;Mensah &Benedict, 2010 andNavirathan, 2018) also revealed that entrepreneurship training has a significant and positive impact on poverty alleviation. Micro-credit and poverty alleviation in both districts have a strong positive relationship and it was statistically significant at the 0.001 level.…”
Section: Correlation Analysissupporting
confidence: 89%
“…Households benefited from credit-plus services by increasing their income through investment projects. Financial non-governmental organizations (FNGOs) offer financial capital (microcredit) and human capital development (entrepreneurship training) to micro and small businesses (MSEs) in Ghana, according to (Atiase et al, 2019). The four primary dimensions utilized to measure microcredit were loan cost, loan size, loan repayment flexibility, and loan accessibility.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The final cluster of CF research features keywords such as “microcredit”, “sustainable development goals”, and “corporate social responsibility”. This cluster demonstrates that scholars are curious about the potential of CF to foster economic growth and social development in emerging economies (Atiase et al. , 2020; Chen and Yuan, 2021).…”
Section: Results Of Co-word Clustering Analysismentioning
confidence: 97%
“…The final cluster of CF research features keywords such as "microcredit", "sustainable development goals", and "corporate social responsibility". This cluster demonstrates that scholars are curious about the potential of CF to foster economic growth and social development in emerging economies (Atiase et al, 2020;Chen and Yuan, 2021). The keyword "microcredit" has a high occurrence frequency, referring to a type of financing that provides small loans to individuals who lack access to traditional banking services (Bhuiyan and Ivlevs, 2019;Jebarajakirthy and Lobo, 2015;Selvaraj et al, 2019).…”
Section: Microcreditsmentioning
confidence: 99%
“…Performance of MSEs can be measured by using sales volume, size of employment, total assets, profit, market share and productivity (Atiase, Mahmood, & Wang, 2019). The dependent variable which is the performance of MSEs in this research paper is proxied by sales volume and size of employees since they are the more objective indicators of firm performance.…”
Section: Operationalization Of Study Variablesmentioning
confidence: 99%